The Level Of Job Satisfaction Affects Teacher Performance At UPT SMPN 18 Medan - Dewi Sri Indriyani; Aman Simaremare (Journal of General Education and Humanities, 2026)
Teacher performance is a key determinant of educational quality, as teachers play a central role in the learning process. However, variations in teacher performance are often linked to differences in job satisfaction, which encompasses aspects such as compensation, leadership, work environment, interpersonal relationships, and opportunities for professional development. This study aimed to examine the effect of job satisfaction on teacher performance at UPT SMPN 18 Medan. The research employed a quantitative approach with a descriptive-correlational design. The population consisted of all teachers at UPT SMPN 18 Medan, and the sample was selected using a non-probability sampling technique. Data were collected through Likert-scale questionnaires measuring job satisfaction and teacher performance. The data were analysed using descriptive statistics and simple linear regression, supported by prerequisite tests for normality, linearity, and heteroscedasticity. Hypothesis testing was conducted using the t-test and the coefficient of determination (R²) at the 0.05 significance level. The results show that job satisfaction has a positive and significant effect on teacher performance. The regression analysis indicates that job satisfaction accounts for 32.8% of teacher performance, while the remaining 67.2% is influenced by other factors not examined in this study. These findings suggest that improving teachers’ job satisfaction can enhance their performance. Therefore, school management is encouraged to prioritise strategies that promote job satisfaction to improve teacher performance and achieve educational goals.